The deconstruction of equity : activist shareholders, decoupled risk, and corporate governance - Ringe, Wolf-Georg, 1976- (Oxford : Oxford University Press, 2016)
New investment techniques and new types of shareholder activists are shaking up the traditional ways of equity investment that inform current corporate law and governance. This book evaluates different risk-decoupling strategies and makes the case for regulatory intervention, developing a comprehensive proposal to address the regulatory problem.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 2, 2016).
Keywords: Investments -- Law and legislation; Stocks -- Law and legislation; Law